Utility of Aprepitant in the Management of Pediatric Patients with Cyclical Vomiting Syndrome - Aravind Thavamani; Sindhoosha Malay; Jasmine Khatana; Sujithra Velayuthan; Senthilkumar Sankararaman (Medicines)
Introduction: Cyclical vomiting syndrome (CVS) is a recurrent debilitating illness characterized by intense episodes of nausea and emesis with widely varied pharmacological management across the country. Aprepitant is now increasingly used in patients with CVS. The impact of aprepitant as an abortive therapy in the readmission of pediatric patients with CVS is currently unknown. Methodology: We analyzed all pediatric patients with a primary diagnosis of CVS using the ICD-10 code in the Pediatric Health Information System database of the Children’s Hospital Association. We evaluated the demographic data, comorbid conditions, and management details during the inpatient stay. CVS patients who received aprepitant during their inpatient hospitalization were compared with patients without aprepitant use. Seven-day readmission rate for CVS was used as the outcome variable to assess the effectiveness of the aprepitant in aborting an episode. Propensity score matching was used to match the two cohorts. Results: We analyzed 1775 patients of which 96 received aprepitant during the inpatient hospitalization. The aprepitant group had a more severe hospitalization course as evidenced by an increased duration of hospital stay (5 vs. 3 days) and total hospitalization costs ($11,790 vs. $6380). There were no significant differences in the 7-day (17% vs. 16%, p = 0.91) readmission rate and results were not altered by propensity score matching. Conclusions: Aprepitant use as an abortive therapy did not affect the 7-day CVS-related readmission rate. Further prospective studies are needed to explore the role of aprepitant as an abortive agent in the management of CVS in the pediatric population.